The Effect of Accountability, Socialization, and Aid Suitability on Human Resource Quality among Underprivileged Scholarship Recipient Students - Hadi Purnomo; Mokhamad Natsir; Harianto Respati (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to describe and analyze the effects of accountability, program dissemination, and the appropriateness of assistance on human resource quality among students from economically disadvantaged backgrounds who receive scholarships in Magetan Regency. This study employed a quantitative approach with an explanatory research design. The study population consisted of 161 students who received scholarships for economically disadvantaged students in Magetan Regency in 2024. A census sampling method was applied, whereby all members of the population were included as research respondents. Data were collected using a Likert-scale questionnaire and analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS version 3.2.9. The findings indicate that accountability has a positive and significant effect on human resource quality. Program dissemination also has a positive and significant effect on human resource quality. Similarly, the appropriateness of assistance has a positive and significant effect on human resource quality and is identified as the most dominant variable. The findings confirm that improving the human resource quality of scholarship recipients requires transparent and accountable program management, effective dissemination of information, and assistance that corresponds to the recipients’ academic needs and socioeconomic circumstances. This study is expected to provide evaluative input for the Government of Magetan Regency in improving the accuracy of beneficiary targeting, the quality of program management, and the sustainability of the scholarship program